2018
DOI: 10.7287/peerj.preprints.26990v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The gut microbiome correlates with conspecific aggression in a small population of rescued dogs (Canis familiaris)

Abstract: Aggression is a serious behavioral disorder in domestic dogs that endangers both dogs and humans. The underlying causes of canine aggression are poorly resolved and require illumination to ensure effective therapy. Recent research links the compositional diversity of the gut microbiome to behavioral and psychological regulation in other mammals, such as mice and humans. Given these observations, we hypothesized that the composition of the canine gut microbiome could associate with aggression. We analyzed fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Future studies identifying commensal bacteria that positively or negatively modulate aggression would deepen our understanding and have potential implications utilizing commensal bacteria to modulate aggressive behaviors. Recently, it was reported that the microbiome correlated with conspecific aggression in a small population of dogs 58 , highlighting that the microbiome may be useful for diagnosing aggressive behaviors prior to their manifestation and potentially discerning cryptic etiologies of aggression. Third, that microbiome synergizes with diet to promote aggressive but not other innate behaviors in our study is intriguing, especially given that Drosophila in the wild may be challenged with scare, dynamic, and highly diverse diets.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies identifying commensal bacteria that positively or negatively modulate aggression would deepen our understanding and have potential implications utilizing commensal bacteria to modulate aggressive behaviors. Recently, it was reported that the microbiome correlated with conspecific aggression in a small population of dogs 58 , highlighting that the microbiome may be useful for diagnosing aggressive behaviors prior to their manifestation and potentially discerning cryptic etiologies of aggression. Third, that microbiome synergizes with diet to promote aggressive but not other innate behaviors in our study is intriguing, especially given that Drosophila in the wild may be challenged with scare, dynamic, and highly diverse diets.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive, anxiety and phobia behavioral disorders can be considered as stress responses with an increase in glucocorticoid (GC) secretion mediated by the hypothalamic-pituitary-adrenal (HPA) axis [20,21]. Although recent works on canine microbiome have investigated potential interactions with aggression, these studies have focused on the variations of their GM profile after targeted dietary interventions to reduce aggressive behaviors [22,23]. To the best of our knowledge, no study has focused on the comparison of the GM structure between dogs exhibiting aggressive, phobic and normal behavior, with specific associations with adrenocortical activity.…”
Section: Introductionmentioning
confidence: 99%